O desenvolvimento do empreendedorismo corporativo: um estudo em empresas do ramo atacadista de pequeno porte do município de Parintins-AM. - Alfaia, Carla Vieira (Brasil, 2023)
This research had as general objective to identify the corporate entrepreneurship strategies used by the entrepreneurs of the four small companies of the wholesale branch of the Municipality of Parintins/AM. For this, as specific objectives, it was necessary to show existing cases in the last 5 (five) years about corporate entrepreneurship in contemporary times; understand the skills needed to continually increase corporate entrepreneurship; propose improvements in the strategies developed by the researched companies. Methodologically, it was a Bibliographic and Descriptive Research, essentially supported by the studies of Corso, Eckert and Pompermayer (2020); Dornelas (2008); Fernandes (2018); Ferreira et al. (2020); Freitas and Manhães (2016); and Maffessoni (2018), among other scholars on the topic addressed. As a research tool, content analysis was used with a qualitative approach. The research method used was the Exploratory one, covering as subjects 4 (four) entrepreneurs of the small wholesale branch of the city of Parintins. The research period was from May to August 2022. For this purpose, as research instruments, an Interview applied to entrepreneurs was applied, in addition to Observation. The study carried out in four companies in the wholesale branch of Parintins-AM showed that the implementation of corporate entrepreneurship strategies can bring significant results for the improvement of management and business growth. Innovation, the development of new products and services, the search for strategic partnerships and the appreciation of employees are some of the fundamental aspects that contribute to the success of corporate entrepreneurship. Therefore, it is important for companies to be aware of business opportunities and encourage an entrepreneurial culture in their work environment, always seeking to improve their ability to innovate and adapt to market changes.